Evaluating temporal changes in water quality due to urbanization: a multi-year observational study in Khalid Khor, Sharjah, UAE - Ahmed, Norhan; Mohammad, Areej; Knuteson, Sandra L.; Samara, Fatin (Frontiers in Marine Science, 2025)
IntroductionUrbanization has profound impacts on aquatic ecosystems, often altering water quality through increased pollutant loads and hydrological changes. This study investigates the long-term temporal variations in key water quality parameters in Khalid Khor, Sharjah, UAE, from 2007 to 2023, to assess the influence of urban development on the aquatic environment.MethodsWater quality indicators including pH, dissolved oxygen (DO), total dissolved solids (TDS), electrical conductivity, temperature, and coliform concentrations were analyzed. Descriptive statistics, box plots, and scatter plots were used to visualize trends, while the Kruskal–Wallis test and Mann–Whitney U test were applied to determine statistically significant differences across years.ResultsThe analysis revealed a significant increase in temperature, peaking in 2017 (p = 0.0002), indicative of urban heat island effects and reduced water flow. Electrical conductivity increased notably after 2015, with distinct spikes in 2011 and 2014 likely associated with urban runoff events. TDS levels rose markedly in 2014, followed by a steady decline through 2023, suggesting changing pollutant discharge patterns. Coliform concentrations were highest in 2007, with significant reductions observed in subsequent years (e.g., p = 0.0070 for 2007 vs. 2022), pointing to improvements in wastewater management. DO levels exhibited a decline around 2016, possibly due to warmer temperatures and nutrient enrichment. pH values remained generally stable (8.0–8.5), with anomalies such as in 2015 (p = 0.0001), potentially linked to industrial discharges.DiscussionThese findings highlight the considerable influence of urbanization on the water quality of Khalid Khor, with significant temporal shifts in physical, chemical, and biological parameters. The study underscores the necessity for continuous monitoring and the implementation of robust water management strategies to mitigate the adverse effects of urban expansion. Sustained regulatory interventions are critical to preserving water quality and ensuring the ecological integrity of urban water bodies in the face of ongoing development.